2023
DOI: 10.1161/jaha.122.029071
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility for the 4 Pharmacological Pillars in Heart Failure With Reduced Ejection Fraction at Discharge

Domenico D'Amario,
Daniele Rodolico,
Agni Delvinioti
et al.

Abstract: Background Guidelines recommend using multiple drugs in patients with heart failure (HF) with reduced ejection fraction, but there is a paucity of real‐world data on the simultaneous initiation of the 4 pharmacological pillars at discharge after a decompensation event. Methods and Results A retrospective data mart, including patients diagnosed with HF, was implemented. Consecutively admitted patients with HF with reduced ejection fraction were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Various studies have indicated that in clinical practice, a high number of patients with HF would be eligible for treatment with SGLT2i [ 18 , 19 ]. In fact, in a recent study that analyzed the eligibility of the four pharmacologic pillars for treatment of HFrEF at discharge from hospital, SGLT2i were more frequently prescribed than RAAS inhibitors and mineralocorticoid receptor antagonists, with kidney failure being the main factor limiting prescription of these agents, in contrast with SGLT2i [ 20 ]. Furthermore, major differences can be observed in the clinical profile and type of HF depending on the specialist treating the patient (e.g., internal medicine vs cardiology).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have indicated that in clinical practice, a high number of patients with HF would be eligible for treatment with SGLT2i [ 18 , 19 ]. In fact, in a recent study that analyzed the eligibility of the four pharmacologic pillars for treatment of HFrEF at discharge from hospital, SGLT2i were more frequently prescribed than RAAS inhibitors and mineralocorticoid receptor antagonists, with kidney failure being the main factor limiting prescription of these agents, in contrast with SGLT2i [ 20 ]. Furthermore, major differences can be observed in the clinical profile and type of HF depending on the specialist treating the patient (e.g., internal medicine vs cardiology).…”
Section: Discussionmentioning
confidence: 99%
“…These studies collectively demonstrate the importance of early initiation, titration, and maintenance of GDMT. Nevertheless, real-world data indicate a number of HF patients are not receiving appropriate medications [19][20][21]. The reasons for this underuse of GDMT may be multifactorial.…”
Section: Importance Of Early Initiation and Maintenance Of Titrated Gdmtmentioning
confidence: 99%
“…However, most clinical data on HF pharmacotherapy have concerned a single drug or two [14][15][16][17], and few studies have evaluated the efficacy of titrating multiple HF agents. Moreover, a number of HF patients do not receive adequate types and doses of HF drugs in the real world, due to low systolic blood pressure and/or heart rate, advanced age, chronic renal insufficiency, electrolyte disturbances, or clinical inertia [18][19][20][21]. To address this underutilization of HF medications, there is definitely a need for practical indicators and criteria that clinicians and medical practitioners can use to promote appropriate drug prescribing.…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent observational study enrolling patients with a first episode of HF hospitalization and a diagnosis of HFrEF, only 46.2% received the four foundational drugs at discharge, considering the contraindications and cautions stated in the European Society of Cardiology HF guidelines for each pillar 21 . Still, adherence to GDMT is associated with the best prognosis in HFrEF, with patients presenting with intolerances or contraindications having the highest risk of events.…”
Section: Figurementioning
confidence: 99%